Palm Oil Mill Effluent (POME) Treatment Using AC/TiO2 Adsorption – Photocatalysis Hybrid Process - Sherlynna Parveen, Anak Deshon Kaman (Universiti Malaysia Sarawak (UNIMAS), 2020)
The vast development of palm oil industry in Malaysia has led to many new technologies that are more economical yet significant for palm oil mill effluent (POME) management in treatment plants. Adsorption process using activated carbon (AC) is one of the popular, effective and widely used treatment methods. However, it is limited by the need of frequent replacement and disposal due to the saturation of contaminants on its surface. On the other hand, photocatalysis process using titanium dioxide (TiO2) is an environmentally friendly method in treating wastewaters; however it is restricted by slow reaction rate and disintegration of TiO2 powder in water. Therefore, this research aims to develop a novel AC/TiO2 hybrid photocatalytic adsorbent (PCA) for POME treatment, which combines AC adsorption and TiO2 photocatalysis to prolong the serviceability of AC. In this study, the adsorption and photocatalysis processes occur simultaneously, which could be described as “capture and destroy” concept. As AC gets saturated over time, the deposited TiO2 activated by UV illumination oxidizes the adsorbed pollutants on AC surface into CO2 and H2O, to regenerate the occupied active sites for further adsorption. Two types of TiO2 coating solutions, the S-TiO2 sol-gel and hybrid S-TiO2+P25 were prepared as a medium for adhesion of TiO2 on AC. P25 is a commercial TiO2 powder to enhance the TiO2 content in the sol-gel. TiO2 deposition was carried out using simple soaking method and calcination to produce three PCAs namely H0 (AC coated with S-TiO2 sol-gel only), H5 (AC coated with 5% hybrid S-TiO2+P25) and H10 (AC coated with 10% hybrid S-TiO2+P25). The PCA were characterized for their physical properties such as TiO2 yield and surface morphology, as well as their treatment performances. The highest TiO2 yield on PCA was achieved for H10 which was 147.25 mg TiO2/g AC, due to high TiO2 P25 content in the hybrid S-TiO2 coating solution. The photocatalytic degradation batch experiments revealed lower efficiency of PCA as compared to AC at initial stage, of both methylene blue (MB) adsorption and POME treatment. This was caused by the deposition of TiO2 which had covered some adsorption sites on AC surface; as visualized through SEM-EDX images, FTIR spectra and reduction in BET surface area. However, upon UV illumination, the removal of MB and POME by PCA were further improved due to photocatalytic reaction by TiO2. The photocatalytic degradation of MB and POME using PCA were best fitted by the pseudo-first-order kinetic model indicating chemisorption. From the life cycle analysis, considering the smaller BET surface area, PCA (H10) showed about 10% higher amount of overall COD removed as compared to AC, and improved the adsorbent deterioration by one cycle. This implied that TiO2 deposition contributed to the cleaning of AC substrate and demonstrated the feasibility to extend the lifespan of AC. Overall, H10 PCA has demonstrated the potential of the photocatalytic adsorbent for POME treatment; however improvisation on the synthesis technique is required for a better sustainability of this wastewater treatment technology. Keywords: Sol–gel, photocatalytic adsorbent, life cycle analysis, lifespan extension